The descent of man : re-envisionings of "the fall" in post-Darwinian novels : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in English at Massey University, Albany, New Zealand - Irvine, Anaise (Massey University, 2010)
In On the Origin of Species, Darwin presented a revised creation narrative which contradicted and superseded the Judeo-Christian narrative in Genesis. His second significant text, The Descent of Man, reflects in its title the ideological and philosophical impact his ideas have had in reversing the anthropocentric assumptions of humanism. This research examines how Darwinian theories have been mediated by science writers and incorporated by literary critics and authors, with emphasis on the representation of Edenic archetypes and the renegotiation of hierarchical relationships between animal, human, and posthuman forms. The thesis is divided into two parts. Part One explores critical responses to Darwinism. In popular science writing, a renewed emphasis has emerged on the dominance of human nature over nurture, and human activities (including art and culture) have been explained in terms of their adaptive functions. In literary criticism, the new school of Literary Darwinism has begun reading texts as expressions of biological drives. Part Two uses a modified form of Literary Darwinism to analyse pairs of literary texts which negotiate the anxieties raised by the implications of Darwinian theory. The Island of Doctor Moreau (1896) and Brave New World (1932) express the fear that mad scientists might exploit their knowledge of evolutionary science to create new, genetically altered species whose freedoms are curtailed by their creators. As Darwinian evolution gained credence, later novels turned away from fear of the scientist and towards fear of the science. Works such as Lord of the Flies (1954) and Galapagos (1985) explore the notion of human as beast, depicting biological and/or societal ‘devolution’ scenarios in which humanistic higher reasoning loses ground to animalism. More recent novels have combined the fears of mad scientists and devolved humanity to imagine future societies in which the genetic alteration of humans is controlled and politicised. In Oryx and Crake (2003), one dangerous and errant mind genetically extinguishes the human race and creates, in its place, a race of naive and unsophisticated posthumans. And in Genesis (2006), the human race is merely something to be studied by a post-apocalyptic chimp-android hybrid species which is physically devolved, but sufficiently advanced intellectually to have conquered humanity. In all of these novels, the depictions of alternative and future societies run alongside re-envisionings of the ‘fall of man’. In their Darwinian updates of the Fall, authors imagine evolutionary biology to be the Tree of Knowledge from which their Adams and Eves eat. Their new societies thus become alternate (inverted) versions of Eden; however rather than the lost paradise of Genesis, these Darwinian Edens are prisons which leave residents trapped and stripped of their humanity.
Keywords: Evolution in literature; Fall of man in literature; English fiction; 20th century